KEBERTAHANAN KOSAKATA PERTANIAN DALAM BAHASA KONJO PADA SISWA KELAS 3 SMP NEGERI 31 BULUKUMBA KABUPATEN BULUKUMBA - Fitriani Basri; Wa Ode Halfian (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
The research is aimed to describe the rate of survival of the vocabulary of agriculture in language Konjo on students grade 3 SMP Negeri 31 Bulukumba in District Bulukumba. The method that is used is the approach qualitative supported by the analysis of quantitative. The collection of data is done by using the 2 ( two ) ways , namely : questionnaire technique ( questionnaire ) and interview technique ( interview ). The results of the study have demonstrated that of the 100 vocabulary that is submitted to the 51 respondents , there is one respondent with knowledge of vocabulary highest is 91% and the knowledge of the lowest 29%. For every vocabulary knowledge on the whole respondents, survival highs are in the vocabulary of god , canggoren , workshops , asu , bembe, and rarely with the level of viability highest is 100%. While the lowest is cakkuru with a percentage of 5,88%. So for the final results the vocabulary survival level in all questionnaires is 64,96%. Keywords : vocabulary, Konjo Language, environment agriculture